Input reconstruction by feedback control for the Schlögl and FitzHugh-Nagumo equations - Maksimov, Vyacheslav I.; Trlötzsch, Fredi (Zielona Góra: Uniwersytet Zielonogórski)
Dynamical reconstruction of unknown time-varying controls from inexact measurements of the state function is investigated for a semilinear parabolic equation with memory. This system includes as particular cases the Schlögl model and the FitzHugh-Nagumo equations. A numerical method is suggested that is based on techniques of feedback control. An error analysis is performed. Numerical examples confirm the theoretical predictions.
Keywords: semilinear parabolic equation; input reconstruction